2014
DOI: 10.1042/bj20131361
|View full text |Cite
|
Sign up to set email alerts
|

Acute nutrient regulation of the mitochondrial glutathione redox state in pancreatic β-cells

Abstract: The glucose stimulation of insulin secretion by pancreatic β-cells depends on increased production of metabolic coupling factors, among which changes in NADPH and ROS (reactive oxygen species) may alter the glutathione redox state (EGSH) and signal through changes in thiol oxidation. However, whether nutrients affect EGSH in β-cell subcellular compartments is unknown. Using redox-sensitive GFP2 fused to glutaredoxin 1 and its mitochondria-targeted form, we studied the acute nutrient regulation of EGSH in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
4
20
0
4
Order By: Relevance
“…They also confirmed the observation in human islets [6]. But whether there is a relation between mitochondrial glutathione redox state and GSIS still remains unknown.…”
Section: Introductionsupporting
confidence: 61%
“…They also confirmed the observation in human islets [6]. But whether there is a relation between mitochondrial glutathione redox state and GSIS still remains unknown.…”
Section: Introductionsupporting
confidence: 61%
“…Increasing glucose produced a reductive shift in matrix thiol redox potential in adenoviral transfected rat islet clusters (504) or INS1-E cells (300). However, no glucose-dependent change in signal was detected from an untargeted, cytosolic, GRX1-roGFP2 probe (504). The implication is that the matrix NADP(H) and glutathione pools respond conventionally to changes in substrate supply, but that this is not transmitted into the cytosol within the time courses of these studies.…”
Section: B Glutathione Poolsmentioning
confidence: 80%
“…The generation and amplification of adenoviruses coding GRX1–roGFP2, mt-GRX1–roGFP2, or mt-SypHer under the control of the cytomegalovirus (CMV) promoter and of an adenovirus coding the red fluorescent protein DsRed under the control of the rat insulin promoter (Ad-RIP-DsRed) were described previously [11], [18], [19]. Adenoviruses coding WT mouse NNT together with mCherry (Ad-NNT) or mCherry alone (Ad-mCh) under the control of the CMV promoter were from Vector Biolabs (Philadelphia, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Using the glutathione redox probe GRX1-roGFP2, we showed that the rise in NAD(P)H autofluorescence, which mainly occurs in mitochondria [10], correlates with a decrease in mitochondrial glutathione oxidation in rat and human β-cells, suggesting that mitochondrial NAD(P)H and glutathione redox state may play a role in GSIS [11]. Mitochondrial NADPH is typically produced by nicotinamide nucleotide transhydrogenase (NNT), isocitrate dehydrogenase (IDH) 2 and malic enzyme (ME) 3 [3], [12].…”
Section: Introductionmentioning
confidence: 96%